Gram–negative antibiotic resistance - Ramos, Maria Helena da Silva Santos (2010)
The emergence and spread of resistant microorganisms is a global problem which has worsened over the past two decades, especially in hospital, compromising the effectiveness of most antibiotics used in clinical practice. Will come under discussion the prevalence of E. coli and Klebsiella species producing extended-spectrum â - lactamases (ESBLs), Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella pneumoniae, to possess a carbapenem- hidrolyzing â - lactamases, as well as the growing increase in ciprofloxacin resistance in several bacterial species. The evaluation of clinical and economic impact of such resistance, and present strategies for their control is also an objective of this work witch is based on data on the evolution of these strains in some Portuguese hospitals from 1994 to 2007.